Analisis Tes dalam Kitab Durusullughah al-'Arabiyah Jilid 1 Karya Imam Zarkasyi dan Imam Syubani - Amy Fitriani Siregar; Siti Nurhasana Mokodompit; Muhajir Muhajir; Nila Alfiroh (University of Darussalam Gontor, 2024)
A good test form can measure student’s real abilities and trigger students' cognitive abilities. The main problem in this study, whether the test form in the Durūs Al-Lughah Al-Arabiyyah book has met good criteria based on the cognitive domains. This study aims to analyze the test in the book of Durūs Al-Lughah Al-Arabiyyah by Imam Zarkasyi and Imam Syubani. This book is widely used in various institutions, and gave birth to many Arabic language experts, Therefore, the researcher wanted to analys the assessment and evaluation structure of the tests in this book. This research uses a qualitative literature study research method. This research method is carried out using descriptive analysis, which is a form of research that provides an organized description of the entire Arabic test to be studied. The results obtained from this research are: First, the form of tests is mostly in the form of memory questions (objective tests) and the form of fill-in questions (subjective tests), and second, the advantages of the book Durūs Al-Lughah Al-Arabiyyah volume 1 are that it is very good for beginners who want to learn the language. Complete with Arabic language material; vocabulary, text, images, to various tests, then the disadvantage is that it uses several objective tests that are commonly used. Keywords: Assessment, Arabic, Literature, Durūs Al-Lughah Al-Arabiyyah, Test